2014
DOI: 10.1155/2014/549721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pumpkin Seed Oil on Hair Growth in Men with Androgenetic Alopecia: A Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: Pumpkin seed oil (PSO) has been shown to block the action of 5-alpha reductase and to have antiandrogenic effects on rats. This randomized, placebo-controlled, double-blind study was designed to investigate the efficacy and tolerability of PSO for treatment of hair growth in male patients with mild to moderate androgenetic alopecia (AGA). 76 male patients with AGA received 400 mg of PSO per day or a placebo for 24 weeks. Change over time in scalp hair growth was evaluated by four outcomes: assessment of standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 21 publications
1
52
0
1
Order By: Relevance
“…The pumpkin extract group had more hair after treatment at the baseline than the placebo group (P < 0.001). The mean hair count improved by 40% in the pumpkin extract group at 24 weeks [8].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The pumpkin extract group had more hair after treatment at the baseline than the placebo group (P < 0.001). The mean hair count improved by 40% in the pumpkin extract group at 24 weeks [8].…”
Section: Discussionmentioning
confidence: 94%
“…Cho et al [8] suggested that pumpkin extract blocks the action of 5-alpha reductase and has antiandrogenic effects on rats [21,22]. In clinical trials, after 24 weeks of treatment, the self-rated improvement score in the pumpkin extract group was higher than in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their multiflorane-type triterpenes have melanogenesis inhibitory activity and thus may be potential skin whitening agents (36). Pumpkin seed oil has shown to be effective for the treatment of hair growth in male patients with mild to moderate androgenetic alopecia (37). Table I summarizes the medicinal and pharmacological effects of Cucurbita sp.…”
Section: Botanical Aspectsmentioning
confidence: 99%
“…Pumpkin seed oil (PSO, family Cucurbitaceae) has been used for treating symptomatic benign prostatic hyperplasia through its inhibitory effect on 5α-reductase and antiandrogenic effect [60,61]. In a randomized, double-blind, placebo-controlled study, self-rated improvement score, and self-rated satisfaction scores in the PSO-treated group were higher compared with the placebo group after oral administration of PSO at dosage of 400 mg/day for 24 weeks.…”
Section: Pumpkin Seed Oilmentioning
confidence: 99%